Pengaruh Intellectual Capital, Good Corporate Governance dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Dewi Rahmawati; Dirvi Surya Abbas; Djenny Sasmita (Akuntansi, 2023)
The purpose of this study was yo determine the effect of Intellectual Capital, Good Corporate Governance and Firm Size on Value of the Firm in manufacturing companies listed on the Indonesia Stock Exchange. The time period used is 4 years, from 2018-2021. The populations of this study includes all manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2021 with total 194 companies and a sample of 39 companies was obtained with purposive sampling method. The number of observation data is 156 data. The type of data used is secondary data. The method of data analysis in this research is panel data regression using Eviews 12 program. The result of this study showed that Intellectual Capital has a positive effect. Good Corporate Governance has no effect and Firm Size has a negavite effect on Value of the Firm.